Simple Hybrid Integration of SiC MOSFETs in a B6 Converter for Enhanced Partial Load Efficiency - Sebastian Gick; Markus Pfeifer; Sebastian Nielebock; Mark-M. Bakran (IEEE Open Journal of Power Electronics, 2025)
This paper introduces a hybrid B6 converter that employs IGBTs as high-side switches and SiC MOSFETs as low-side switches. By integrating a modified Space Vector Pulse Width Modulation scheme, the converter achieves near-SiC efficiency during partial load operation of a three-phase industrial motor. Remarkably, it utilizes only half the SiC area of a full SiC converter, making it both cost-effective and straightforward to implement. A motor model is defined to analytically assess the impact of semiconductor loss mechanisms and establish criteria for an efficient industrial motor converter. Simulations based on empirical measurements are conducted to optimize the SiC/Si ratio and generate efficiency curves for the converters under investigation. The results demonstrate that the hybrid converter can reduce partial load losses by two-thirds compared to a conventional IGBT converter. These simulations are validated by experimental loss measurements on a prototype converter, confirming the high accuracy of the simulation results. The proposed converter offers significant advantages, including high flexibility, ease of implementation, and increased power density, with only a moderate rise in converter cost.